Navigating Interprofessional Education: A Qualitative Process Evaluation Examining Leadership Perspectives in Online IPE Curriculum Design and Implementation - Senyo Agbeyaka; Sara A. Harper; Vicki Simonsmeier; Maria Kleinstäuber (Journal of Continuing Education in the Health Professions, 2026)
Introduction: Interprofessional education (IPE) remains an important component of curriculum training among health and allied health trainees. Additional research is needed regarding the challenges for facilitators in implementing such educational endeavors. Method: Therefore, this qualitative study examined the perspectives of those leading the IPE process and facilitators in planning and implementing an online real-time (synchronous) university-based IPE curriculum. Results: Respondents (n = 7) described the following nine themes that facilitated or challenged the planning and implementation of the IPE curriculum: (1) shared vision and commitment to implementing IPE, (2) emphasizing core competencies in interdisciplinary collaboration, (3) engagement and effort, (4) importance of buy-in, (5) maximizing experiential education, (6) balancing faculty involvement and expectations in IPE development, (7) balancing educational content for diverse experience levels, (8) challenges in staffing continuity for sustaining IPE initiatives, and (9) need for dedicated leadership and resources in IPE implementation. Discussion: These findings explore IPE implementation among a unique constellation of professions that are rarely included in IPE literature and can provide insight for starting, re-evaluating, and improving IPE education and practice.